1989
DOI: 10.1128/aem.55.4.940-945.1989
|View full text |Cite
|
Sign up to set email alerts
|

Changes in concentrations of coenzyme F420 analogs during batch growth of Methanosarcina barkeri and Methanosarcina mazei

Abstract: Coenzyme F420 has been assayed by high-performance liquid chromatography with fluorimetric detection; this permits quantification of individual coenzyme F420 analogs whilst avoiding the inclusion of interfering material. The total intracellular coenzyme F420 content of Methanosarcina barkeri MS cultivated on methanol and on H2-C02 and of Methanosarcina mazei S-6 cultured on methanol remained relatively constant during batch growth. The most abundant analogs in M. barkeri were coenzymes F420-2 and F420-4, whils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Thus, the CoM content per cell varied little with the growth phase. The same trend was found for coenzyme F 420 in methanogens (31). We observed that the amount of CoM per milligram of protein varied by up to a factor of 7 among organisms, which was comparable to the factor of 5 associated with the previously described CoM bioassay (5).…”
Section: Resultssupporting
confidence: 87%
“…Thus, the CoM content per cell varied little with the growth phase. The same trend was found for coenzyme F 420 in methanogens (31). We observed that the amount of CoM per milligram of protein varied by up to a factor of 7 among organisms, which was comparable to the factor of 5 associated with the previously described CoM bioassay (5).…”
Section: Resultssupporting
confidence: 87%
“…The reduced cofactor F 420 supplies reduction equivalents for the stepwise covalent binding of the second and third hydrogen atom in methanogenesis (CH–CH 2 –CH 3 ) and is oxidized during the process. The quantification of cofactor F 420 in pure culture extracts has been realized using either HPLC [ 19 , 20 ] or assays with the ADP-linked hydrogenase system of Methanobacterium bryantii M.o.H [ 21 ]. The concentrations measured with either technique varied from 120 to 410 mg kg −1 cell mass (wet) for hydrogenotrophic methanogenic archaea but were considerably lower for organisms conducting non-hydrogenotrophic methanogenesis like Methanosarcina sp.…”
Section: Introductionmentioning
confidence: 99%
“…C oenzyme F 420 , a deazaflavin derivative with two to eight glutamate residues in the side chain ( Fig. 1A) (1)(2)(3)(4), is found in a wide range of archaea and bacteria, including methanogens, where it serves major roles in catabolism (5,6). In mycobacteria, it facilitates redox transformations of cell wall lipids, neutralization of oxidative and nitrosative stress, and degradation of aromatic compounds (7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Our report concerns the reaction that incorporates glutamate residues in the side chain of F 420 . We describe the product of this reaction as F 420 -n, where n is the number of glutamate residues that are linked almost exclusively via ␥-linkages (1)(2)(3)(4). In mycobacteria and late-evolving methanogenic archaea, such as Methanosarcina species, the value of n is two to eight (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation